2013
DOI: 10.1002/bmc.3024
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalysis of tolvaptan, a novel AVP‐V2 receptor antagonist in human plasma by a novel LC‐ESI‐MS/MS method: a pharmacokinetic application in healthy South Indian male subjects

Abstract: A simple, rapid and sensitive liquid chromatography/electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) assay method is proposed for the determination of tolvaptan in human plasma samples using tolvaptan d7 as internal standard (IS). Analyte and the IS were extracted from 100 μL of human plasma via simple liquid-liquid extraction. The chromatographic separation was achieved on a C18 column using a mixture of methanol and 0.1% formic acid buffer (80:20, v/v) as the mobile phase at a flow rate of 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The maximal plasma concentration was determined to be about 160 ng/mL 3 h after a single oral administration of 15 mg in healthy male subjects. Published methods for the determination of tolvaptan in plasma involve the use of liquid‐liquid extraction (LLE), solid‐phase extraction (SPE), or protein precipitation for sample preparation. Sample analysis is performed by high‐performance liquid chromatography coupled to tandem mass spectrometry (HPLC‐MS/MS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal plasma concentration was determined to be about 160 ng/mL 3 h after a single oral administration of 15 mg in healthy male subjects. Published methods for the determination of tolvaptan in plasma involve the use of liquid‐liquid extraction (LLE), solid‐phase extraction (SPE), or protein precipitation for sample preparation. Sample analysis is performed by high‐performance liquid chromatography coupled to tandem mass spectrometry (HPLC‐MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“… Published methods for the determination of tolvaptan in plasma involve the use of liquid‐liquid extraction (LLE), solid‐phase extraction (SPE), or protein precipitation for sample preparation. Sample analysis is performed by high‐performance liquid chromatography coupled to tandem mass spectrometry (HPLC‐MS/MS). An excretion of less than 1% of the unchanged drug in urine is described in literature .…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, chromatography and validation details were not provided in these reports [2] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , which might have little guiding significance for reproducing or developing the determination methods of tolvaptan. This was achieved by Pei et al, [5] and Derangula et al [14] . In this paper, we developed and validated a highly sensitive, simple and specific LC–MS/MS method for determination of tolvaptan in rabbit plasma using LLE for the first time.…”
Section: Introductionmentioning
confidence: 86%
“…Literature retrieval revealed that there were few methods reported for quantitation of tolvaptan in biological matrices [2] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . As of now, to our knowledge, a few studies on tolvaptan pharmacokinetics have been reported [2] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . The LC–MS/MS methods for determination of tolvaptan described in these papers have several obvious shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…A few methods using a liquid chromatography (LC) coupled to tandem mass spectrometry (MS/MS) have been developed for determination of tolvaptan in human plasma. 11,16,17 However, tolvaptan metabolites in human plasma have been only rarely measured to date. 11 They reported simultaneous quantitation method of tolvaptan and two carboxylates including DM-4103 using samples taken from volunteers who received tolvaptan.…”
Section: Introductionmentioning
confidence: 99%